2017
DOI: 10.1111/1750-3841.13605
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cellular and Animal Models for the Study of Antioxidant Activity: A Review

Abstract: The mechanisms of antioxidant activities of phytochemicals are highly complex, so various methods to study them have been developed. However, the diverse available methods show inconsistent results. Different stressors, cell models, and animal models have been used to evaluate the antioxidant properties of phytochemicals. However, the literature still lacks a summary of the effects of different stressors, cell models, and animal models on the evaluation of antioxidant activities. Therefore, the mechanisms of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 128 publications
0
27
0
6
Order By: Relevance
“…It is also good complementary information in addition to the ABTS-based antioxidant measurement. Indeed, it helps to underline mechanisms in complex systems; to be effective, the antioxidants need to be absorbed, transported, distributed, and retained properly in the biological fluids, cells, and tissues [41]. In addition, to be used in food, medicine, or cosmetics, the antioxidant molecule must be safe/non-toxic.…”
Section: Discussionmentioning
confidence: 99%
“…It is also good complementary information in addition to the ABTS-based antioxidant measurement. Indeed, it helps to underline mechanisms in complex systems; to be effective, the antioxidants need to be absorbed, transported, distributed, and retained properly in the biological fluids, cells, and tissues [41]. In addition, to be used in food, medicine, or cosmetics, the antioxidant molecule must be safe/non-toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes such as superoxide dismutase (SOD) and glutathione peroxidase (GPx) are synthesized in the body and provide protection from reactive oxygen species generated during heat stress (Gupta et al, 2013). These antioxidants scavenge both intracellular and extracellular super oxides and inhibit lipid peroxidation of plasma membrane (Zhang, et al, 2017). Chaudhary et al (2015) reported a significantly higher level of plasma malondialdehyde, SOD and GPx activities in Surti buffaloes during hot humid periods and hot dry periods indicating an increased free radical production during periods of heat stress.…”
Section: Blood Biochemical Responsementioning
confidence: 99%
“…27 Tissue MDA and GSH-Px levels and SOD activity are indices of oxidative stress and lipid peroxidation, as well as of free radical clearance and antioxidant capacity. [28][29][30][31] Compared to the untreated HLP rats (Fig. 5), ARFE-H rats have signicantly higher SOD activity (P < 0.05), and lower GSH-Px levels (P < 0.05).…”
Section: Liver Sod Mda and Gsh-px Analysismentioning
confidence: 92%